68.9k views
5 votes
Which expression is equivalent to -3 2/3

Which expression is equivalent to -3 2/3-example-1
User Acbay
by
6.4k points

2 Answers

3 votes

Answer: -3 -2/3

Step-by-step explanation: Got it right on TTM

Which expression is equivalent to -3 2/3-example-1
User CyberEternal
by
6.1k points
4 votes

Answer:


-3(2)/(3) equivalent to
-3-(2)/(3)

Explanation:

Given:
-3(2)/(3)

We need to choose equivalent to given expression.

First we simplify the given expression mixed number to fraction.


\Rightarrow -3(2)/(3)


\Rightarrow -(3\cdot 3+2)/(3)


\Rightarrow -(9+2)/(3)


\Rightarrow -(11)/(3)

Option 1:
-3+(2)/(3)


\Rightarrow (-9+2)/(3)=-(7)/(3)\\eq -(11)/(3)

False

Option 2:
-3-(2)/(3)


\Rightarrow (-9-2)/(3)=-(11)/(3)= -(11)/(3)

True

Option 3:
3-(2)/(3)


\Rightarrow (9-2)/(3)=(7)/(3)\\eq -(11)/(3)

False

Option 4:
3+(2)/(3)


\Rightarrow (9+2)/(3)=(11)/(3)\\eq -(11)/(3)

False

Hence,
-3(2)/(3) equivalent
-3-(2)/(3)

User Tomalec
by
5.9k points